ANALYSIS OF JOB PROMOTION AND JOB TRAINING ON EMPLOYEE PERFORMANCE WITH WORK ABILITY AS AN INTERVENING VARIABLE AT THE DEPARTMENT OF EDUCATION AND CULTURE OF MEDAN CITY, NORTH SUMATRA PROVINCE - Saiful Riza; Mesra B; Elfitra Desy Surya (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study aims to analyze the effect of job promotion and job training on employee performance, with job ability as an intervening variable at the Medan City Education and Culture Office, North Sumatra Province. The problem raised in this study is the suboptimal improvement of employee performance even though promotion and training programs have been implemented. This study uses a quantitative approach with a survey method. The research sample consisted of 113 permanent employees at the Elementary School and Guidance unit, selected by total sampling. The data analysis technique used Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results showed that there were two rejected hypotheses, namely job promotion had a positive but insignificant effect on employee performance and job training on performance through employee ability and five more hypotheses were accepted. These findings indicate that improving individual competence is key to optimizing the results of human resource management policies. Therefore, it is recommended that organizations continue to encourage performance-based promotions and training that is in accordance with work needs to improve employee performance as a whole.